Following the Open-Source Trail Outside the Digital World: The Case of Open-Source Seeds - Elsa Tsioumani; Mike Muzurakis; Yannis Ieropoulos; Asterios Tsioumanis (tripleC: Communication, Capitalism & Critique)
In this article, we assess the application of the open-source development model in the field of agricultural research and development, as a potential tool for upholding both public scientific research, and farmer-led innovation and farmers’ rights. First, we provide an overview of the problems associated with the rise of IPRs in agriculture in view of global challenges such as food security and environmental sustainability, and present the debate on farmers’ rights, including its rationale and international policy and legal responses. We then review open source initiatives in the digital domain, including successes and shortcomings, and offer our understanding of relevant terminologies. We explore the parallels between software development and innovation in agriculture and review ongoing open-source agriculture-related initiatives. We particularly address the potential for open-source systems to address existing asymmetries in capabilities and contribute to global challenges such as food security.